Ghost-eye : a novel - Ghosh, Amitav, 1956- (New Delhi, India : Fourth Estate, 2026)
"Past and present collide in a novel about a girl who just might be a "case of the reincarnation type.""-- Provided by publisher.
AAL
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
Keywords: Fiction; Calcutta (India) -- Fiction; Families -- Fiction; Historical fiction; Novels